Racionalidade(s) dos sojicultores familiares do Sudoeste Paranaense - Angelita Bazotti (Ciências Sociais Unisinos)
Calculation of production costs suggests that economic viability of soybean crop is higher in more extensive areas, where gains of scale are higher. However, family farmers have kept this activity for many generations, defying the purely economic logic of efficiency and profitability. Having this in mind, the main goal of this paper is to understand the rationality, strategies, and motivations of family farming involved in soybean production, based on a field research with farmers in Capanema, located in the southwest of Paraná. The empirical evidence gathered in the region reveal some endogenous factors related to culture of the rural population, know-how on soybean production, tradition, and possibilities given by favorable soil and climate. The different combinations of these factors explain the resilience of family farmers in growing soybean, despite the existing economic difficulties.